Phenomenological Synthesis of Cultural Understanding Among Senior High School Research Classes - Adlit, Marlon F. (Future Science / FSH-PH Publications, 2021)
The development of student's skills in the conduct of research, both qualitative and quantitative, is envisioned in the K to12 curriculum. This study uses qualitative research to show students' perceptions and understanding of a particular issue. Similarly, it describes apparent cultures postulated within the students' chosen themes. Finally, it determines the development of cultural knowledge in the context of Merleau-Ponty's phenomenology of perception among Grade 11 students at a Senior High School near Laguna Lake in the City of San Pedro, Laguna, Philippines, during the school year 2016-2017. Semi-structured interviews, focus group discussions, and triangulation was used to obtain students' cultural understanding and share their experiences undertaking diverse qualitative research using purposive sampling. The data was analyzed using phenomenological analysis. Students' perceptions and streams of consciousness include street children, child labor fishermen, and school violence. Cultural understanding encompasses (a) the economic and psychological implications of family, (2) camaraderie, pakikisama and pakikiisa, and (3) education as a survival strategy. Senior High School students' research experiences connect underpinnings of cultural understanding.